A game‐theoretic model for resource allocation with deception and defense efforts. Issue 3 (17th February 2019) - Zhang, Xiaoxiong; Hipel, Keith W.; Ge, Bingfeng; Tan, Yuejin
Abstract: This paper develops a strategy for assisting two players in allocating multiple resources in a strategic sequential game. The defender first needs to allocate deception and defense efforts among targets to deceive the attacker and strengthen the target, respectively. Then, the attacker chooses a type of threat and a target to attack. The defender aims at mitigating the possible damage to the targets, whereas the attacker strives to cause maximum damage to the targets. Traditional modeling approaches typically focus only on the defender's homogeneous resource in defense and are not well suited to effectively capture the complex interplay between players. Given scarce resources, a game‐theoretic model is proposed for determining optimal strategies for both players. The key novel features of this model include: (1) the attacker's learning and the defender's counter‐learning efforts are considered; (2) trade‐offs between deception and defense efforts among different targets for the defender are investigated; and (3) sensitive analysis is carried out to see how different parameters can affect the equilibrium results. An illustrative example is presented to demonstrate the procedure of this game‐theoretic model and show its effectiveness. The results can provide additional insights for defense and deception strategies.